THE EFFECT OF ENTREPRENEURIAL ORIENTATION AND INNOVATION ON BUSINESS PERFORMANCE MEDIATED BY COMPETITIVE ADVANTAGE (SURVEY ON UMKM IN CULINARY SECTOR IN SUKABUMI CITY) - Syifa Aulia Yudistira; R. Deni Muhammad Danial; Resa Nurmala (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Entrepreneurial Orientation, Innovation, and Competitive Advantage on Business Performance in culinary MSMEs in Sukabumi City. The results indicate that: (1) Entrepreneurial Orientation significantly influences Business Performance with a t-value of 3.509 > 1.96 (t-table) at a 5% significance level; (2) Innovation significantly influences Business Performance with a t-value of 3.121 > 1.96; (3) Competitive Advantage also significantly influences Business Performance with a t-value of 3.571 > 1.96; (4) Competitive Advantage mediates the influence of Entrepreneurial Orientation on Business Performance with a Sobel Test result of 4.147 > 1.96; and (5) Competitive Advantage mediates the influence of Innovation on Business Performance with a Sobel Test result of 3.061 > 1.96. These findings suggest that strengthening entrepreneurial orientation, innovation, and competitive advantage can enhance the performance of MSMEs in the culinary sector. The implications of this study highlight the need for integrated strategies to optimize these factors to support the growth and competitiveness of MSMEs.